Beykoz Honor a Robust Online Exam Platform System - Elkhodary, Abdullah I.; Erkan , Feyza; Aburas , Abdurazzag A. (SOTVI, 2025)
In today’s digital landscape, online assessments have emerged as a pivotal element of educational systems worldwide. However, the rise of online examinations has also been accompanied by a troubling increase in cheating incidents. Research highlights that the most prevalent forms of online exam fraud include unauthorized access, screen sharing among students, and impersonation of test-takers. In response to these challenges, we introduce